31 Fabry disease in east asia. (24th April 2019) - Lee, Alex PW; Kam, Kevin KH; Fung, Erik; Chow, Josie; Fan, Yiting; Teekakirikul, Polakit; Wong, Katak; Chan, Joseph YS; Chan, David; Sheng, Bun
Abstract : Fabry disease (FD) is an X-linked inherited lysosomal storage disorder that results from mutations in the α-galactosidase A gene ( GLA ), leading to deficient alpha-galactosidase A (α-GalA) activity and subsequent accumulation of globotriaosylceramide (Gb3) in a variety of tissues. 1 The estimated prevalence of classic FD in males ranges from 1:8000 to 1:117, 000, 2 likely an underestimation given its non-specific manifestations. The mutation IVS4 +919G>A (c.936+919G>A) associated with founder effect in East Asia was first described in Taiwan. 3 Left ventricular hypertrophy (LVH) is a hallmark of the later-onset cardiac variant of FD. The prevalence of FD among adult patients with LVH is unknown. In an ongoing FD screening programme from August 2017 through 2018, we measured plasma α-GalA activity using dried blood spot testing in 143 consecutive male patients with LVH (defined as maximal LV wall thickness ≥13 mm on echocardiography). Patients with low α-GalA activity underwent GLA gene sequencing analysis and endomyocardial biopsy. Four of 143 patients with LVH (2.8%) had low plasma α-GalA activity (0.4±0.2 μmol/L wb/hr; 3%–15% of the mean in normal controls). All 4 unrelated patients (aged 53–74 years) shared the same IVS4 +919G>A mutation with maximal LV wall thickness ranging from 14–29 mm. None had extracardiac manifestations but presented with hypertrophic cardiomyopathy, hypertension, heart failure, or aortic stenosis. Endomyocardial biopsy performed in one patient showed hypertrophic cardiomyocytes with sarcoplasmic vacuolisation. Our results suggest that FD should be considered as a cause of LVH in adult men even when other more usual causes of LVH are present. References: Germain DP. Fabry disease. Orphanet J Rare Dis 2010;5:30. Meikle PJ, Hopwood JJ, Clague AE, Carey WF. Prevalence of lysosomal storage disorders. JAMA 1999;281:249. Lin HY, Chong KW, Hsu JH, Yu HC, Shih CC, Huang CH, Lin SJ, Chen CH, Chiang CC, Ho HJ, Lee PC, Kao CH, Cheng KH, Hsueh C, Niu DM. High incidence of the cardiac variant of Fabry disease revealed by newborn screening in the Taiwan Chinese population. Circ Cardiovasc Genet 2009;2:450.